2022
DOI: 10.3389/fpsyt.2022.989171
|View full text |Cite
|
Sign up to set email alerts
|

The concept of Narcissistic Personality Disorder–Three levels of analysis for interdisciplinary integration

Abstract: In this paper, I distinguish three different levels for describing, and three corresponding ways for understanding, deficient empathy as the core of NPD (Narcissistic Personality Disorder). On the macro level, deficient empathy can be explained as disturbed interpersonal functioning, and is understood as lack of recognition. On the meso-level, deficient empathy can be described as psychic disintegration, and can be understood specifically in its dissocial aspects. Psychic disintegration in NPD correlates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…The results remained consistent regardless of the measurement methods used, which included a video-task and the Interpersonal Reactivity Index (IRI). This finding aligns with recent studies including meta-analyses investigating the relationship between narcissism and affective empathy (Vonk et al, 2013;Chukwuorji et al, 2020;Urbonaviciute and Hepper, 2020;Eddy, 2021;Jacobs, 2022;Simard et al, 2022;di Giacomo et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results remained consistent regardless of the measurement methods used, which included a video-task and the Interpersonal Reactivity Index (IRI). This finding aligns with recent studies including meta-analyses investigating the relationship between narcissism and affective empathy (Vonk et al, 2013;Chukwuorji et al, 2020;Urbonaviciute and Hepper, 2020;Eddy, 2021;Jacobs, 2022;Simard et al, 2022;di Giacomo et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…One contributing factor to these inconsistencies is measurement methods, which range from self-report assessments to behavioral tasks. Data from different tasks show that empathy in narcissism is not solely characterized by deficiency but can also vary due to motivational factors ( Baskin-Sommers et al, 2014 ; Hepper et al, 2014a ; Jacobs, 2022 ). Pajevic et al (2018) found that despite higher self-report cognitive empathy among narcissistic individuals, this did not translate to better performance in emotion recognition tasks, which showed a nonsignificant correlation.…”
Section: Introductionmentioning
confidence: 99%
“…The onset and maintenance of paranoid oikeiôsis can be caused by relations that show a lack of recognition or are based on false recognition [cf. (104)(105)(106)(107)] or manipulative environments [e.g., (108)] and are the roots of an erosion of basic trust. What has to be mentioned is that for PPD, the experiences of being manipulated, controlled, or betrayed can be suggested as an impairing factor for developing a stable intuitive sense of self, others, and the world ((109), 118ff), because if one constantly has to question the validity or reality of one's experiences, this can lead to constantly doubting the realness of one's subjective experiences and to anticipate subjection to threats or shaming (110).…”
Section: Changes Of Intuition In Paranoid Oikeiôsismentioning
confidence: 99%
“…This may become more plausible when we stress the developmental aspect of social cognition (61)(62)(63). Through the recognitional "interactive" modes of imitation, joint attention, as well as affective contagion, we can presuppose a priority of recognition over cognition from a biopsychosocial developmental perspective (24,64). Consequently, the perception of a lack of social relatedness or suffering from the pain of social disconnectedness would not even be possible without the all-important (basically affective) experiences of previous interactions that impregnate our brains (61).…”
Section: Human Companionship: Recognition First!mentioning
confidence: 99%